Imagens cativas: uma análise das representações da escravidão negra a partir de livros didáticos de história aprovados pelo pnld 2017 - Mariano, Tiago de Souza (2019)
This research analyses the way in which black slavery and afro-Brazilian culture are represented through images in history books in the final years of Elementary School. The research focused on textbooks of History approved by the Plano Nacional do Livro Didático (PNLD) 2017, specifically two collections published by FTD and two published by SARAIVA. Information on the State of Knowledge has been collected. It should be noted that these collections have not yet been analyzed in their iconographic collection, making this work original and necessary. As a theoretical-methodological reference, it is used by historians and researchers who deal with didactics for teaching history, such as Bittencourt (2004; 2015) and Munakata (2007) who recommend the textbook as an instrument for knowledge construction and deconstruction. As for representations’ study and images, the stand outside are Chartier (1990), Paiva (2006), and Mauad (2014). Authors like Munanga are available; Gomes (2016), Gonçalves e Silva (2007) who discuss blackness and africanity in curriculums. This research has a qualitative and exploratory nature, as it intends to investigate and analyze the image black slavery in textbooks authorized by PNLD 2017. As for the methodology, it has a documentary analysis about imagery texts from defined categories based on Bardin's contents analysis (2011). Starting from this approach, the goal is to verify possible changes and permanency of Afro-descendants representation in the history curriculum